Differentiability of the objective in a class of coefficient inverse problems. (1st June 2017) - Smołka, Maciej
Abstract: In this paper we study the Fréchet differentiability of the objective functional for a quite general class of coefficient inverse problems. We present sufficient conditions for the existence of arbitrary-order differentials as well as formulae for the calculation of first and second order derivatives. The general case theorems are then applied to two real-world geophysical inverse problems.